2016
DOI: 10.1111/cmi.12572
|View full text |Cite
|
Sign up to set email alerts
|

Identification of class II ADP-ribosylation factors as cellular factors required for hepatitis C virus replication

Abstract: GBF1 is a host factor required for hepatitis C virus (HCV) replication. GBF1 functions as a guanine nucleotide exchange factor for G-proteins of the Arf family, which regulate membrane dynamics in the early secretory pathway and the metabolism of cytoplasmic lipid droplets. Here we established that the Arf-guanine nucleotide exchange factor activity of GBF1 is critical for its function in HCV replication, indicating that it promotes viral replication by activating one or more Arf family members. Arf involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 61 publications
3
32
0
Order By: Relevance
“…The Arf4 antibody also produced punctate labeling in the cytoplasm, but identical staining was observed in Arf4 -/- cells suggesting that it represents nonspecific staining (Fig 2C, 2F and 2H). These results indicate that the primary localization of Arf4 in ciliated cells is in the cis-medial Golgi rather than trans Golgi or cilium, a conclusion consistent with localization of GFP-tagged Arf4 [29]. …”
Section: Resultssupporting
confidence: 57%
“…The Arf4 antibody also produced punctate labeling in the cytoplasm, but identical staining was observed in Arf4 -/- cells suggesting that it represents nonspecific staining (Fig 2C, 2F and 2H). These results indicate that the primary localization of Arf4 in ciliated cells is in the cis-medial Golgi rather than trans Golgi or cilium, a conclusion consistent with localization of GFP-tagged Arf4 [29]. …”
Section: Resultssupporting
confidence: 57%
“…During poliovirus infection, GBF1 is also recruited early to RNA replication sites. However, in this case, the colocalization is still visible at later time points (56), in line with the existence of differences of GBF1 involvement in HCV and poliovirus replication (33,57).…”
Section: Discussionsupporting
confidence: 81%
“…However, the involvement of this kinase during HCV genome replication is still controversial (28)(29)(30)(31)(32). Moreover, we recently demonstrated that the function of GBF1 during HCV genome replication is not mediated by Arf1 and is distinct from its regulatory functions with respect to the cellular secretory pathway and the morphology of the Golgi complex (33). GBF1 function in HCV replication is mediated by the pair Arf4 and Arf5, whereas its function in the regulation of the secretory pathway is mediated by the pair Arf1 and Arf4 (33,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Enteroviruses, which belong to the family Picornaviridae, rely on both protein and lipid components of the host secretory pathway to provide the structural foundation of their replication complexes (17). Recently, the guanine nucleotide exchange factor GBF1 and its effector ADP ribosylation factor 1 (Arf1), known to regulate Golgi membrane trafficking and organelle structure in the secretory pathway, were identified as host factors required for efficient HCV replication (18)(19)(20)(21). This requirement suggests that Golgi components have a role in HCV replication.…”
Section: Significancementioning
confidence: 99%